Identification of patterns of crystal-chemical transformations in historical artifacts made of metals - Indutnyi, Volodymyr; Merezhko, Nina; Pirkovich, Kateryna; Andreiev , Oleksii (Eastern-European Journal of Enterprise Technologies, 2021)
The theoretical substantiation of the process of elimination of individual chemical elements from crystal lattices of metals in the process of the crystal-chemical transformations taking place during the long history of artifact existence was given. To confirm the theoretical conclusions, five ancient gold items from different historical periods (from the IV century B.C. to the XVIII century A.D.) with approximately the same contents of gold, silver, copper, and iron in the alloy body were studied. The conducted studies will promote more exact attribution of historical artifacts made of metals and revealing the signs of forgery or restoration. The chemical composition of items was determined immediately under patina and in the alloy body using a scanning electron microscope equipped with an energy dispersion spectrometer. The results have shown a much lower gold content inside the alloy than in the item surface. At the same time, the undamaged surface cleansed of mineral crusts contained significantly fewer impurities than the polished surface which did not have contact with the environment. Therefore, the study of the chemical composition of gold artifacts cannot be conducted solely based on surface studies. The studies have resulted in establishing a dependence of the concentration of the main component (gold) of the alloy in the artifact surface on the item age in thousands of years. Equations for predicting the age of the items that are chemically belonging to the described item group were also presented. Studies of peculiarities of crystal-chemical processes are very important in practice to prove the historical artifact authenticity, adjust artifact dating, identify signs of forgery or profound changes caused by restoration